2018
DOI: 10.1080/24748668.2018.1525651
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the three-dimensional kinetics and kinematics of maximal effort punches among amateur boxers

Abstract: The purpose of this study was to quantify the 3D kinetics and kinematics of six punch types among amateur boxers. Fifteen males (age: 24.9 ± 4.2 years; stature: 1.78 ± 0.1 m; body mass: 75.3 ± 13.4 kg; boxing experience: 6.3 ± 2.8 y) performed maximal effort punches against a suspended punch bag during which upper-body kinematics were assessed via a 3D motion capture system, and ground reaction forces (GRF) of the lead and rear legs via two force plates. For all variables except elbow joint angular velocity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 41 publications
1
72
0
Order By: Relevance
“…Perhaps surprisingly, there was no associated improvement in technique in the novices who demonstrated minimal changes in angular velocity of the trunk (-1.78% and 2.50%) for both Retention 1 and 2, respectively. Thus, their improved bag acceleration (6.88% and 9.67%) must have come from increased movements of the more distal body segments, such as the elbow ( Stanley et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps surprisingly, there was no associated improvement in technique in the novices who demonstrated minimal changes in angular velocity of the trunk (-1.78% and 2.50%) for both Retention 1 and 2, respectively. Thus, their improved bag acceleration (6.88% and 9.67%) must have come from increased movements of the more distal body segments, such as the elbow ( Stanley et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The jab requires rapid and complex motor skills, involving a series of coordinated and forceful muscular contractions ( Lenetsky et al., 2020 ). Stanley et al. (2018) found that the jab exhibited a proximal-distal sequence for the shoulder and elbow joints, respectively, with the shoulder reaching peak angular joint velocity approximately 12% before the elbow during jab execution.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although this might be the case in a boxing match for a better positioning on the ring or to maintain a good balance in front of an opponent, this opinion was not confirmed by our data and previous data collected in laboratory conditions. In novice amateur boxers, Stanley et al ( 2018 ), reported that the lead or rear leg may present a higher or lower GRF depending on the punch type and technique of execution (i.e., rear or lead hand). As recorded in our study, and based on other throwing activities such as the shot put, discus throw, javelin, and baseball, it seems that a stable lead leg (presenting the highest GRF) be necessary to produce force proximally to the end of the kinematic chain (i.e., the most distal segment which is the fist) (Whiting et al, 1991 ; Bartonietz, 1994 ; Macwilliams et al, 1998 ; Dinu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, access to the above performance staff and their resources may differ between elite and non-elite boxers. An effective punch in boxing requires rapid proximalto-distal sequencing, culminating in high peak fist velocities toward the target prior to impact [16][17][18]. Recent research has demonstrated acute increases in the velocity of combat striking and throwing techniques, following a PAPE conditioning activity comprising elastic resistance [19,20].…”
Section: Introductionmentioning
confidence: 99%